Cancer-specific and overall survival in patients with recurrent prostate cancer who underwent salvage extended pelvic lymph node dissection. Issue 1 (December 2016) - Osmonov, Daniar; Aksenov, Alexey; Trick, David; Naumann, Carsten; Hamann, Moritz; Faddan, Amr; Jünemann, Klaus-Peter
Abstract Background The aim was to evaluate cancer-specific survival (CSS) and overall survival (OS) in patients with prostate cancer (PCa) recurrence who underwent salvage extended pelvic lymph node dissection (ePLND), taking into consideration pre- and postoperative androgen deprivation therapy (ADT). Methods Salvage ePLND was performed in a cohort of 54 patients with PCa recurrence, and data from 45 patients were analyzed. The indications for salvage ePLND were biochemical recurrence (BCR) of PCa and suspect findings on11 C-choline PET/CT. PSA-level, biochemical response (BR), duration of biochemical recurrence freedom (BCRF), number of metastases, OS and CSS were analyzed retrospectively. Results The average follow-up was 42.7 ± 20.8 months. Thirty-three patients (73.3 %, 95 % CI: 60.5–83.6 %) achieved BCRF during follow-up. The mean BCRF-period was 31.4 ± 19.7 months. CSS and OS were both 91.7 % ± 4.8 % (3-year survival) and 80.6 ± 8.6 % (5-year survival). Twenty-four patients (53.3 %, 95 % CI: 40.0–66.3 %) with castration-resistant PCa (CRPC) responded again to ADT after salvage ePLND. Conclusions Salvage ePLND for selected patients with BCR and clinically recurrent nodal disease can achieve an immediate complete PSA response (i. e. BCRF) in nearly half of the patients. Patients with CRPC responded again to ADT after ePLND. Multicenter prospective studies with a control group are needed.